Mémoire du monde : patrimoine filmique national / Programme général d'information et UNISIST - ONUESC (1995)

Évaluation de procédés commerciaux de désacidification de masse - Tse, Season (Institut canadien de conservation (ICC), 1995)
he evaluation of three mass deacification processes – Akzo-{DEZ}, Wei T’o and {FMC}-{MG}3 – is a five-part project that began in August 1991. The project, coordinated by Helen Burgess and the Metro Toronto Chairman’s Committee for Preserving Documentary Heritage ({CCPDH}), is funded by a large number of libraries, archives and institutions in Canada and the United States, and is supported by {CCI}. The goal is to identify the potential and limitations of the three mass deacidification processes. The results will provide technical information for institutions that are considering mass deacidification as a solution to the problem of acid papers. The five groups of materials to be studies are listed, a project description is given and some general observations and conclusions are made in this article.